Evidence-based clinical standard for the diagnosis and treatment of candidemia in critically ill patients in the intensive care unit - Jorge Alberto Cortés; Martha Carolina Valderrama-Rios; Paula M. Peçanha-Pietrobom; Moacyr Silva Júnior; Cándida Diaz-Brochero; Rafael Ricardo Robles-Torres; Carmelo José Espinosa-Almanza; Laura Cristina Nocua-Báez; Marcio Nucci; Carlos Arturo Álvarez-Moreno; Flavio Queiroz-Telles; Ricardo Rabagliati; et al. (Brazilian Journal of Infectious Diseases)
Candidemia is the predominant form of invasive candidiasis and the most frequently occurring serious fungal infection in critically ill patients in Intensive Care Units (ICU). Studies carried out in Latin America reveal a higher incidence of candidemia and higher mortality rates when compared to North America or Europe. This highlights the need to develop guidelines for correctly diagnosing and treating candidemia in critically ill patients in the ICU. These guidelines are part of the efforts to implement antifungal optimization programs in the region to obtain better clinical outcomes and promote rational antifungal use. This evidence-based clinical standard, established through expert consensus for the Latin American context, contains recommendations and algorithms for diagnosing and treating candidemia in critically ill ICU patients.